Implementation of Buying and Selling Gold on DSN-MUI Fatwa Number 77/DSN-MUI/V/2010 Concerning Non-Cash Buying and Selling of Gold - Handoko, Luqman Hakim; Akbar, Nashr; Izzah, Ahmad (Sharia Faculty Islamic Economic Law Study Department, 2024)
This study aims to review the literature about the implementation of fatwa DSN-MUI Number 77 on gold installments or non-cash basis. The permissibility of gold installment by MUI attracted debate and research among researchers on its implementation as the text of hadith considered the gold installment as riba which is the central issue in Islamic economics and finance. Selected Literature Review (SLR) analysis were adopted. The data was retrieved from Google Scholar using PoP Software. The observation found 29 articles related to the implementation of the fatwa. The result offered that in implementing fatwa number 77 can be grouped into 4 categories. The first is the group whose results were compliance with the fatwa with 18 articles. Second, articles state that implementation is not following the fatwa are 7 articles. Third, three articles did not clearly state whether they were shari’ah compliance or not. Fourth, research that just explains the legality of fatwa number 77. Therefore, it suggested to the Shari’ah supervisor board to closely monitor and supervise its implementation of Fatwa.